Hypertension and Type-2 Diabetes in Bangladesh : Continuum of Care Assessment and Opportunities for Action - World Bank (World Bank, Washington, DC, 2020)
In order to address the large and growing non-communicable disease (NCD) burden, Bangladesh’s public health system needs to change and innovate. It needs to transition from a system designed for infectious disease and mother & child health to an integrated care system with focus on primary health care, out-patient and chronic care, as well as community health promotion. This report presents findings from an NCD cascade analysis, using hypertension as a tracer condition as well as type-2 diabetes, in order to determine the continuum of care for chronic NCDs in Bangladesh. The cascade findings are embedded in a review of the country’s policy and health care delivery environment for NCDs and a benchmarking assessment against similar economies and regional comparator countries. The report also presents promising practices and models of NCD and chronic care in Bangladesh and elsewhere. Based on the evidence reviewed and analyses conducted, the report provides recommendations for different aspects of NCD policy and programming. These are meant to provide input into the dialogue on how to improve NCD integrated care and outcomes in Bangladesh. The support is provided within the World Bank’s assistance to countries to strengthen NCD care through data-driven resource allocation and decision-making.